Zur Zukunft des Wirtschaftsstandorts Deutschland: sortierende Bemerkungen - Michael Hüther; Melinda Fremerey; Simon Gerards Iglesias (Wirtschaftsdienst, 2024)
Am 7. Februar 2024 fand in Berlin die gemeinsame Konferenz von Wirtschaftsdienst und dem Institut der deutschen Wirtschaft (IW) unter dem Titel "Zur Zukunft des Wirtschaftsstandorts Deutschland" statt. Dieser Beitrag diente als Keynote zur Eröffnung der Konferenz. Bei der Frage nach der Ausgangssituation des Wirtschaftsstandorts, der Standortqualität, dem Standortwettbewerb und der Standortpolitik ist nicht von vornherein klar, an welcher Norm sich der Befund und damit die Lösung orientieren soll. – – This article served as the keynote speech at the opening of the conference 'On the Future of Germany as a Business Location', hosted by Wirtschaftsdienst and the German Economic Institute. The standards and indices used to assess the competitiveness of industrial locations evolve over time, leading to potential variations in results and policy implications. Current policies face the dual challenge of navigating both change and competition among locations. Therefore, industrial policy should increasingly prioritise the capacity for transformation and the availability of necessary input factors to establish a foundation for successful transformation and maintain competitiveness.
Keywords: L50; R38; 330; Standort; Standortpolitik; Deutschland; Standort; Standortpolitik; Deutschland